Extractive Distillation of Ethanol/Water with 1-Butyl-3-Methylimidazolium Bromide Ionic Liquid as a Separating Agent: Process Simulation - Hartanto, Dhoni; Handayani, Prima Astuti; Astuti, Widi; Kusumaningtyas, Ratna Dewi; Purwana, Yulian Candra; Maftukhaturrizqiyah, Maftukhaturrizqiyah; Wijayanti, Reni Titis; Wulansari, Durroti Zuhriah; Wulansarie, Ria; Pradnya, Irene Nindita; Hadikawuryan, Danang Subarkah; Wibowo, Agung Ari; Sholihin, Riza Mazidu; Chafidz, Achmad; Khoiroh, Ianatul (ASEAN Journal of Chemical Engineering, 2023)
Ethanol purification has become of great interest recently because ethanol can be used as renewable energy, solvent in many industries, and for medicinal purposes. The separation of ethanol from water is challenging because the azeotropic point has appeared in this binary mixture. Extractive distillation technology is one of the most interesting methods to separate ethanol from water due to the competitiveness of its energy consumption and capital investment costs. Ionic liquids such as 1-butyl-3-methylimidazolium bromide [BMIM] [Br], categorized as a green solvent, produce a significant salting-out effect in the ethanol-water system. This makes ionic liquid a promising solvent in ethanol-water separation. This study simulated the extractive distillation of an ethanol-water system with 1-butyl-3-methylimidazolium bromide as a solvent. The simulation and sensitivity analysis were performed on the Aspen Plus Process Simulator to obtain the optimum configuration. The NRTL thermodynamic model was used in this study. The effects of the number of stages (NS), binary feed stage (BFS), entrainer feed stage (EFS), and reflux ratio (RR) on the ethanol concentration with minimum energy requirements were studied. The most optimal configurations to produce a high ethanol concentration with less energy are NS 28, BFS 22, EFS 4, and RR 1.5.